Paraconsistent logic approach for active noise reduction - de Carvalho Junior, Arnaldo; Justo Filho, João Francisco; de Oliveira, Alexandre Maniçoba; de Oliveira, Charles Artur Santos; Da Silva Filho, João Inacio (Journal of Mechatronics Engineering, 2020)
The Active Noise Reduction (ANR) is widely used in aircraft, headsets, telecommunications and medicine systems, to reduce or eliminate noise, while maintaining the characteristics of the desired signal. In this article a network of paraconsistent artificial neural cells (PANC) will be presented, based on the paraconsistent annotated logic by 2 values annotations (PAL2v) that allows to operate as ANR. Simulations indicate that the results presented by ANRPAL are better than those obtained by classic filters.